The Influence of Giving Lemon Aromatherapy on Pregnant Women with Emesis gravidarum - Meteria Simbolon; Fitriyaningsih; Trifonia MK Koli (Science Midwifery, 2022)
Emesis Gravidarum experienced by about 70-80% of pregnant women and is a phenomenon that often occurs at 5-12 weeks of gestation. Lemon essential oil is one of the herbal oils that is considered a safe remedy for pregnancy. The purpose of this study was to find out the description of giving Lemon therapy to pregnant women with emesis gravidarum in pregnant women at the Maubesi Health Center in 2022. This research method is a quantitative type of quasi-experiment with a One Group Pretest-Postest Design approach without control. The research location will be held at the Maubesi Health Center on March 24-May 5, 2022. The population in this study were all pregnant women who had a pregnancy checkup on March 24-May 5, 2022 at the Maubesi Health Center. The number of samples was 10 pregnant women with emesis gravidarum which were taken by purposive sampling based on inclusion and exclusion criteria. Research results From the results of research conducted by obtaining the frequency of nausea and vomiting before being given inhalation of Lemon aromatherapy obtained an average value of 7.4 and the frequency of nausea and vomiting before being given inhalation of Lemon aromatherapy obtained an average of 0.1 There is an effect of giving inhalation of Lemon aromatherapy to morning sickness in pregnant women with P-value = 0.000. The conclusion is that there is a statistically significant difference between before and before the intervention of giving inhalation of Lemon aromatherapy. Therefore, it is recommended that pregnant women who experience vomiting can apply Lemon aromatherapy treatment to reduce nausea and vomiting.